2017
DOI: 10.1152/japplphysiol.00958.2016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of positive pressure ventilation on mean systemic filling pressure in critically ill patients after death

Abstract: Mean systemic filling pressure (P) defines the pressure measured in the venous-arterial system when the cardiac output is nil. Its estimation has been proposed in patients with beating hearts by building the venous return curve, using different pairs of right atrial pressure/cardiac output during mechanical ventilation. We raised the hypothesis according to which the P is altered by tidal ventilation and positive end-expiratory pressure (PEEP), which would challenge this extrapolation method based on cardiopul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Our study differs from this protocol since incremental airway plateau pressures were modified in contrast to PEEP levels, showing slightly lower Pms values which are in line with current and seminal literature [1-4, 8, 10, 11, 29]. Another study focused on the effect of PEEP and tidal ventilation on Pms in deceased patients showed a small but significant increase in Pms as well [32]. Despite indications that PEEP and tidal volumes influence Pms, both Pmsa as Pms-Insp were measured under the same PEEP-levels and tidal volumes during our protocol.…”
Section: Discussionsupporting
confidence: 85%
“…Our study differs from this protocol since incremental airway plateau pressures were modified in contrast to PEEP levels, showing slightly lower Pms values which are in line with current and seminal literature [1-4, 8, 10, 11, 29]. Another study focused on the effect of PEEP and tidal ventilation on Pms in deceased patients showed a small but significant increase in Pms as well [32]. Despite indications that PEEP and tidal volumes influence Pms, both Pmsa as Pms-Insp were measured under the same PEEP-levels and tidal volumes during our protocol.…”
Section: Discussionsupporting
confidence: 85%
“…The presented strong linear relationship between cardiac output and CVP is in line with Guyton's theory on VR (44) and is also observed by multiple studies in both animal models (16,24) and humans (14,19,(45)(46)(47), while in the past they left room for discussion on the linearity when flow approached zero. However, it remains questionable if these CVP versus cardiac output points are part of one single VR curve (24). The increased intra-alveolar pressures and lung expansion with concurrent increase in pleural and pericardial pressure during an IHM might directly modify the characteristics of the VR curve, by shifting the curve or by modifying its slope (20).…”
Section: Reconstructed Vr Curvesupporting
confidence: 84%
“…Suggesting that both parameters are connected, but do not represent the exact same physiological parameter. It is indeed shown that MCFP is not measurable in beating-heart (24,40). Comparing MCFP values between studies is further complicated since the induction of cardiac arrest differs greatly (24,38,41).…”
Section: Correlation With Mcfpmentioning
confidence: 99%
“…Whereas these methods have shown a good correlation with mathematical estimates of MSFP [152], we have recently shown in an experimental model that such extrapolates overestimate the standstill MSFP, as the manoeuvres themselves influence the target measure directly, possibly via hepatosplanchnic waterfalls [39]. Whether inspiration influences MSFP is an ongoing, unresolved debate [39,54,55,154], which warrants caution in the application of these methods. Further research in this field of heart-lung interactions is needed.…”
Section: Estimation Of Mean Systemic Filling Pressure With Respiratory Manoeuvresmentioning
confidence: 95%
“…MSFP is considered to be constant throughout the cardiac cycle due to the large compliance of the vessel system and is assumed to be unaltered during the respiratory cycle [36,37,[50][51][52]. This has been challenged, however [39,[53][54][55].…”
Section: Venous Return and Ventricular Preloadmentioning
confidence: 99%